Emotion regulation-based internet-delivered cognitive behavioural therapy for premenstrual dysphoric disorder: study protocol for a randomised controlled trial in Sweden - Hoppe, Johanna M.; Weise, Cornelia; Kleinstaeuber, Maria; Skalkidou, Alkistis; Vegelius, Johan; Comasco, Erika; Gröndal, Maria; Kaltsouni, Elisavet; Sundström, Felicia; Sampaio, Filipa; Andersson, Gerhard; Buhrman, Monica (BMJ Open, 2025)
Introduction Premenstrual dysphoric disorder (PMDD) is a cyclic mood disorder affecting around 2%-5% of women of reproductive age. Pharmacological interventions exist, but many patients with PMDD experience residual symptoms, discontinue medications or refrain from them due to side effects. Thus, non-pharmacological treatments are needed as an alternative or additive treatment strategy. Evidence indicates that cognitive behavioural therapy (CBT) is a promising candidate. However, further research is required to establish its efficacy and identify ways to improve the treatment. Specifically, incorporating components targeting emotional and interpersonal dysregulation could theoretically enhance its effects. Furthermore, increasing the generally low accessibility of CBT for PMDD necessitates scalable and cost-effective ways to deliver treatment. The current study aims to evaluate the effects and cost-effectiveness of an internet-delivered CBT (ICBT) intervention for PMDD incorporating skills training in emotion regulation and interpersonal effectiveness. Methods and analysis The study is a parallel two-group randomised controlled trial with 1:1 allocation to 8 weeks of therapist-guided ICBT or a waitlist control condition. Following recruitment and inclusion, 164 individuals aged 18-45 years who fulfil the Diagnostic Manual of Mental Disorders-5 criteria for PMDD will be randomly assigned to the two groups. Primary outcomes are pretreatment to post-treatment group differences in premenstrual symptoms and their impact on everyday life, as well as psychological and functional impairment during the premenstrual phase. Secondary outcomes include treatment effects on quality of life and difficulties in emotion regulation. Long-term treatment effects will be assessed 6 and 12 months postintervention. Data will be analysed using latent Gaussian process modelling and linear mixed models. The economic evaluation will analyse individual-level societal costs and outcomes between trial arms. Recruitment is expected to begin in February 2025, with study completion anticipated by February 2028. Ethics and dissemination The study has been approved by the Swedish Ethical Review Authority (2023-00655-01). Results will be disseminated via presentations and publications in international journals and national outlets for clinicians and patients with PMDD. Protocol version PS2024_v1. Trial registration number NCT06496139.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Clinical Trial; eHealth; GYNAECOLOGY; PSYCHIATRY